High prevalence of depressive symptoms in a national sample of adults in Indonesia: Childhood adversity, sociodemographic factors and health risk behaviour - Karl Peltzer (2019)
© 2018 Background: The aim of this study was to investigate depressive symptoms and their association with sociodemographic factors, stressors and support, including childhood adversity, health status risk and behaviour in Indonesia. Method: In a cross-sectional national population survey in 2014–15 in Indonesia, 31442 adults (mean age 37.3 years, SD = 14.9, age range 15–101 years) responded to the Centers for Epidemiologic Studies Depression Scale (CES-D-10) and various other measures. Results: Overall, 15.0% of participants reported moderate and 6.9% severe depressive symptoms, or 21.8% moderate or severe depressive symptoms (21.4% among men and 22.3% among women). In multivariable logistic regression among both men and women, sociodemographic factors (younger age, poor subjective economic background, being unemployed, residing in Java and main island groups), stressors (childhood hunger and poor or fair self-rated health status and having experienced disasters), lack of social trust and religiosity, having one or more chronic conditions, tobacco use and soft drink consumption were positively and obesity negatively associated with moderate or severe depressive symptoms. Conclusion: High rates (21.8%) of depressive symptoms were found. Several risk factors including sociodemographic factors such as younger age, stressors, lack of social support, health risk status and behaviour variables were identified which can be utilized in guiding interventions.